Exposure–response characterisation of tildrakizumab in chronic plaque psoriasis: Pooled analysis of 3 randomised controlled trials. Issue 9 (25th March 2020) - Kerbusch, Thomas; Li, Hanbin; Wada, Russell; Jauslin, Petra M.; Wenning, Larissa
Abstract : Aims: In this exposure–response analysis, the dosing regimen for tildrakizumab, an antibody for treating moderate‐to‐severe chronic plaque psoriasis, was determined using data from 3 randomised controlled trials (P05495/NCT01225731: phase 2b, n = 355; reSURFACE 1/NCT01722331: phase 3, n = 772; reSURFACE 2/NCT01729754: phase 3, n = 1090). Methods: A maximum drug effect (Emax ) logistic‐regression exposure–efficacy model was used to describe the week 12 Psoriasis Area and Severity Index (PASI) responses with average concentration of tildrakizumab during weeks 1–12 (Cavg12 ) as exposure metric. The impact of covariates (e.g., body weight, region) was tested. Exposure–safety, longitudinal pharmacokinetic–pharmacodynamic and risk–benefit analyses were also conducted. Results: At week 12, Emax was estimated at 62.2, 37.9 and 14.6% of responders for PASI75/90/100, respectively. Exposure–response curves plateaued at exposures >5 μg mL −1 . Heavier subjects had a lower response rate to placebo as measured by PASI75/90/100 than lighter subjects. PASI100 placebo response was less in subjects with higher baseline PASI score and older age. Simulated week 12 PASI75 increased by ≤4% on increasing the dose from 100 to 200 mg every 12 weeks (Q12W). The pharmacokinetic–pharmacodynamic model adequately described the time course of PASI change after treatment in the entire population and in each subject. Risk–benefit profiles were favourable for the 100‐ and 200‐mg doses in different weight subgroups. Conclusions: Patients with moderate‐to‐severe psoriasis should receive 100‐mg subcutaneous tildrakizumab Q12W. Patients with high body weight (>90 kg) may benefit from a higher dose (200‐mg Q12W).